2021
DOI: 10.1038/s41598-021-00932-0
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological and social conditions contribute to infectious diarrhea in China

Abstract: Infectious diarrhea in China showed a significant pattern. Many researchers have tried to reveal the drivers, yet usually only meteorological factors were taken into consideration. Furthermore, the diarrheal data they analyzed were incomplete and the algorithms they exploited were inefficient of adapting realistic relationships. Here, we investigate the impacts of meteorological and social factors on the number of infectious diarrhea cases in China. A machine learning algorithm called the Random Forest is util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 106 publications
2
5
0
Order By: Relevance
“…The results highlighted the susceptibility of children aged <5 years; particularly, those aged 0 to 2 years accounted for a significant proportion (196,905/388,636, 50.7%) of the OID cases in Fujian Province. This finding aligns with previous research indicating their susceptibility to OID [42][43][44]. Viral pathogens such as rotavirus, adenovirus, norovirus, and Salmonella were the 4 most common pathogens in China [45].…”
Section: Principal Findingssupporting
confidence: 90%
“…The results highlighted the susceptibility of children aged <5 years; particularly, those aged 0 to 2 years accounted for a significant proportion (196,905/388,636, 50.7%) of the OID cases in Fujian Province. This finding aligns with previous research indicating their susceptibility to OID [42][43][44]. Viral pathogens such as rotavirus, adenovirus, norovirus, and Salmonella were the 4 most common pathogens in China [45].…”
Section: Principal Findingssupporting
confidence: 90%
“…A similar positive relationship between diarrhea and temperature has been reported in Latin America and Africa (Thiam et al 2017). The rapid number of cases of diarrhea increased in China because speed up in relative humidity and temperature (Yang et al 2021). The latest investigation assesses in Nepal, there is a 4.4% greater chance that a child under the age of five will develop diarrhea at 1°C higher in mean temperature (Dhimal et al 2022).…”
Section: Introductionsupporting
confidence: 57%
“…Chou et al ( 2010 ) found that changes in the maximum temperature and extreme rainfall were strongly related to diarrhea-associated morbidity, especially among children (0–14 years) and the elderly (40–64 years). A study in China revealed that diarrhea incidence increased with increase in temperature and relative humidity (Yang et al 2021 ). The latter authors also found that a 1 °C rise in temperature increases the rates of diarrhea cases by 5.6%.…”
Section: Introductionmentioning
confidence: 99%